Barriers to technology adoption, international R&D spillovers and growth - Jesus Crespo Cuaresma; Neil Foster; Johann Scharler (University of Innsbruck, Department of Public Finance, 2007)
Panel data is used to investigate the extent of R&D spillovers between OECD countries, and the importance of barriers to technology adoption in affecting the benefits of such spillovers. Our results indicate that countries with less regulated goods and labour markets benefit more from foreign R&D.
Keywords: O30; O40; C33; 330; R&D spillovers; technology adoption; economic growth; Forschung; Spillover-Effekt; Technologietransfer; Wirtschaftswachstum; Schätzung; OECD-Staaten